THE RELATIONSHIP BETWEEN WORK-LIFE BALANCE AND WORKLOAD WITH BURNOUT IN NURSES - Mauliddiyah, Dwi; Widyastuti, Widyastuti (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The purpose of this study is to see the relationship between work, life, balance and workload with burnout in nurses who work at one of the private hospitals in Sidoarjo. Method: The approach in this research is quantitative correlation. The research sample consisted of 161 nurses selected through random sampling technique from a total of 300 nurses, with a significance level of 5% based on the Issac and Michael table. To collect data, the instrument used was a Likert scale to measure work life balance, workload and burnout variables. The work-life balance variable has a reliability of 0.956 with 36 items, the workload variable has a reliability of 0.765 with 36 items, and the burnout variable has a reliability of 0.973 with 32 items. SPSS 30.0 software was used to analyze data with multiple correlation techniques. Results: The results showed that there was a significant correlation between workload and work-life balance with the level of burnout of nurses. The statistical test results showed a coefficient value of 74.004 and p-value <0.001. This means that this correlation model is significant. It can be concluded that work life balance and workload simultaneously have a significant influence on burnout in nurses. Novelty: Burnout is a condition characterized by physical, emotional, and mental exhaustion as a form of impact from the use of energy that exceeds one's capacity.